Kirsten learns a lesson : a school story - Shaw, Janet Beeler, 1937-; Graef, Renee; Lackner, Paul (Middleton, WI : Pleasant Co., 2000)
After immigrating from Sweden to join relatives in an American prairie community, Kirsten endures the ordeal of a strange school through a secret friendship with an Indian girl.
"1854."
"American Girl."
"2"--Spine.
4.4
3-6
Keywords: Frontier and pioneer life -- Juvenile fiction; Swedish Americans -- Juvenile fiction; Emigration and immigration -- Juvenile fiction; Indians of North America -- Juvenile fiction; Schools -- Juvenile fiction; Frontier and pioneer life -- Fiction; Swedish Americans -- Fiction; Emigration and immigration -- Fiction; Indians of North America -- Fiction; Schools -- Fiction; Historical fiction; Frontier and pioneer life -- Fiction; Swedish Americans -- Fiction; Immigration and emigration -- Fiction; Native Americans -- Great Plains -- Fiction; School stories; Historical fiction